Childhood Behavior Management Strategy based on Fun Learning Environment - Akmal Mundir; Hasan Baharun; Soniya Soniya; Siti Hamimah (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2022)
The impact of the pandemic on student behavior can also be seen in face-to-face learning conducted after the pandemic. Face-to-face learning that was carried out after the pandemic made children feel like starting face-to-face learning that had been done before the pandemic. Thus, this study aims to reveal early childhood behavior management strategies based on a fun learning environment. This research uses a qualitative approach with the type of case study. This study resulted in the findings that early childhood behavior management strategies based on a fun learning environment were carried out by; 1) setting specific, observable, and measurable goals; 2) creating a structured environment with routines and schedules; 3) considering situational and environmental factors; 4) motivate with positive praise and attention, and; 5) cooperate with parents.